Effect of growth and carcass traits on likelihood of early pregnancy in Nellore heifers raised at intensive nutritional plan - Paula Junior, Rones de; Zervoudakis, Joanis Tilemahos; Silva, Felipe Gomes da (Acta Scientiarum. Animal Sciences, 2022)
This study evaluated the influence of the quantitative traits measured by real-time ultrasound (adjusted longissimus muscle area [AdjLMA], adjusted rump fat thickness [AdjRFT], and adjusted marbling [AdjMAR]) as well as age at first breeding [AFB] and adjusted weight [AdjWeight], on the probability of occurrence of early pregnancy (EP) in 55 Nellore heifers, and also performed an economic analysis. All calves received supplementation in creep-feeding (ad libitum), and at weaning (average age= 210 ± 30 days; average weight= 241 ± 33 kg) until first breeding by artificial insemination (May to November) all heifers were managed in the same group (two paddocks of 25 ha each evenly covered with Urochloa Marandu Grass) and received protein-energy supplementation (1% of average BW per animal/day). The quantitative variables were collected immediately after timed artificial insemination (average age= 392 ± 27 days; average weight= 431.90 kg), and the pregnancy diagnosis was completed at 30 days following insemination. For economic analysis, two systems were compared (age at first breeding at 13 and 24 months). The greater adjusted weight on the first breeding increased the probability of occurrence of early pregnancy, while the greater adjusted longissimus muscle area reduced. In addition, intensive meat production systems provide greater economic return throughout cow-calf operation.